Transcended C Editor - Jose, Rinu Rani; Charles, Niya; Varghese, Bessy Anna; Alakananda, (International Journal of Computer Sciences and Engineering, 2025)
Transcended C editor is a software that edits plain texts and comprises of Java Swings and AWT. This project has all the frames prepared in Swing. The Transcended C editor enables us to code C programs more efficiently. This editor is provided with features such as auto completions, signature help, syntax highlighting, string searching, descriptions, different font styles, sizes etc, along with an added option for compilation and run which makes it different from other editors.